A Conceptual Study on Agnikarma- A Review Article - Nayak, Ajay Kumar; Fiaz, Shamsa (International Research Journal of Ayurveda & Yoga, 2024)
Agnikarma, or heat cauterization, is one of Ayurveda’s Anushastras (surgical tool substitutes) or para-surgical techniques. It is said to offer total relief in some chronic ailments that aren’t treated by herbal treatment, surgery, or alkaline cauterization. Ancient Indian surgeon Sushruta prescribed various materials such as Pippali (pipperlongum), Ajasakrut (goat’s excreta), Godantha (cow’s tooth), Shara (arrow), Shalaka (metal rods), Kshoudra (honey), Guda (jaggery), Sneha (oil/fat) etc. for cauterizing specific body parts such as skin, muscle, blood vessels, ligaments, etc. based for various illness conditions, appropriate material should be selected according to the surgeon’s rationale. Agnikarma has a multi-faceted effect on the body. Because of its Tikshna (rapid action), Ushna (hotness), Sukshma (subtle), Vyavayi (fast spreading), and Vikashi (works without being metabolised) properties to eradicate Srotorodha (obstruction in channels of body), it is usually employed in Vata and Kapha diseases.The fundamentals of Agnikarma are attempted to be revealed in this essay.